Mental illness - Espejo, Roman, 1977- (Detroit : Greenhaven Press, 2012)
'Mental Illness: Is Mental Illness a Serious Problem?; How Should Society Address Mental Illness?; What Mental Health Issues Do Youths Face Today?; What Treatments for Mental Illness Are Effective?'--
Includes bibliographical references and index.
Keywords: Mental illness -- Treatment; Mental illness -- Social aspects